Analisis Keselamatan dan Kesehatan Kerja (K3) pada Proyek Otomatisasi Mesin Vacum Pan di Pabrik Gula - Gilang Nur Rosyid; Irwanto Irwanto (Pusat riset dan Inovasi Nasional, 2026)
This research analyzes the implementation of Occupational Safety and Health (K3/OSH) in the automation project of the Vacuum Pan machine at a sugar factory in Indonesia. The Vacuum Pan machine automation project poses high potential hazards due to its involvement with electrical systems, high-pressure pipes, and the installation of electrical and automatic control systems. The research methods used were daily direct observation in the field and interviews with the factory's safety (EHS) personnel, project workers, and interns for one month, from July 7 to August 8, 2025. The results show that K3 planning, such as the availability of HIRADC documents, SOPs, Safety Plans, and K3 facilities (APAR, evacuation routes, safety signs), has been well-implemented and adheres to applicable standards. K3 supervision activities include Safety Inspection (routine twice a week), Safety Patrol (daily and spontaneous), and Safety Talk or Toolbox Meeting (routine every Wednesday). However, the aspect requiring improvement is worker discipline, particularly in the use of Personal Protective Equipment (PPE) and adherence to Standard Operating Procedures (SOPs), which were recorded at compliance frequencies of 65% and 60%, respectively. Workers' response to hazardous situations was also found to be less responsive (50%). In conclusion, while K3 planning and facilities are adequate, the overall K3 implementation needs to be optimized through increased supervision and the establishment of a disciplined culture regarding PPE and SOPs.